Development of dynamic pupillometry apparatus to quantify pupil light reflex for assessment of autonomic dysfunction in patients with type 2 diabetes - A.V Siva kumar; R Padmavathi; Mahadevan Shriraam; K.N Maruthy; K Mahesh Kumar; B Sowjanya (Elsevier, 2024)
Background: Diabetes is a chronic non-communicable disease leading to various microvascular and macrovascular complications. Autonomic dysfunction is one of the early-onset complications of diabetes which goes undetected. The quantitative Pupillary light reflex (PLR) is a sensitive indicator of autonomic failure, which helps to identify these high-risk patients to reduce morbidity, mortality, and economic burden on diabetic care. Objectives: To record and determine altered pupil light reflex variables for evaluating autonomic dysfunction in type 2 diabetic patients. Materials & methods: The study was conducted during 2018-2020. 400 participants were recruited, divided into the diabetic group (n = 200), and healthy volunteer group (n = 200). All participants were evaluated for autonomic status evaluation using Pupillary light reflex and Heart rate variability. Results: All PLR variables are highly significant between the diabetic and healthy volunteer participants including parasympathetic variables (R.L, ACA, MPD, and MCV), sympathetic variables BPD, ADA, RPD, and MDV). All the HRV parameters were within the range of normative data from the Taskforce (1996). The RMSSD, NN50, and pNN50 % significantly differed between the two groups, whereas all frequency domain parameters showed statistically similar results. Conclusion: Autonomic dysfunction in diabetic patients evaluated by PLR, especially parasympathetic dysfunction was detected, which delays the constriction phase and its variables. It is also evidenced by reduced SDNN, RMSSD, and NN50. However, the frequency domain has not shown any variation between the two groups. Thus, the evaluation of PLR aids in the early detection of autonomic dysfunction and the extent of parasympathetic and sympathetic contribution to inadequate PLR response.